(untitled) (Balneo and PRM Research Journal, 2022)
Abstract: Modern rehabilitation procedures use devices that provide physical therapists with various types of information to improve assessment of patient progress during rehabilitation plans. The new trend of these technologies is the development of safe, portable and comfortable wearable devices with extensive applications in various environments (medical clinics or at the patient’s home). The present work presents a portable and safe device for hand rehabilitation, consisting of five finger force sensors and a palmar sensor arranged in the ball, capable of capturing pressure signals during the execution of movements guided by the physiotherapist or by a video game/virtual reality. A 3-axis accelerometer was used to spatially monitor the patient’s movements. A series of games with different levels of difficulty were created, through which the degree of mobility of the patient can be monitored depending on the game he chooses and at the same time reflected by the score obtained at the end of the game. Also, to be more interactive, the interface was chosen to play with 2 players simultaneously. So that they can choose to play in the team or as competitors. The system allows users to show different routines to guide them in their use and also evaluates pressure signals and response time. Keywords: microcontroller, games interactive, physiokinetotherapist, rehabilitation, health improvement.